THE INFLUENCE OF SOCIODRAMA METHOD TOWARD STUDENTS’ SPEAKING SKILL AT TEN GRADE OF SMKN 4 BATAM IN THE ACADEMIC YEAR 2017/2018 - Juwita Boneka Sinaga; Icha Wany Pangaribuan (Universitas Riau Kepulauan, 2018)
Abstract The aim of this research was carried out to find the influence of using sociodrama method in teaching speaking for ten grade of junior high school at SMKN 4 Batam whether there is significance different in speaking achievement of the students who are taught using a sociodrama and those who are taught without sociodrama. The subjects of the study were 76 students. The method used in this study was quasi experimental study with Non Equivalent Control Group design. The researcher divided two classes into an experimental class and a control class. Before the treatment, the researcher did a pre-test in both classes. Moreover, the researcher taught speaking by a sociodrama method in the experimental class. The last, the researcher conducted a post-test in both. After that, she calculated independent sample t-test to analyze the data. Value of the significant was 0.000 and significant level 5% was 0.05. As the result, the value of significant was lower than significant level. It can be concluded that the using of sociodrama method able to encourage the students to affective in teaching speaking and the hypothesis tested in this study was accepted.Keywords: Speaking skill, Sociodrama Method.